A Randomized Comparative Trial on the Therapeutic Efficacy of Topical Aloe vera and Calendula officinalis on Diaper Dermatitis in Children. (19th April 2012) - Panahi, Yunes; Sharif, Mohamad Reza; Sharif, Alireza; Beiraghdar, Fatemeh; Zahiri, Zahra; Amirchoopani, Golnoush; Marzony, Eisa Tahmasbpour; Sahebkar, Amirhossein
Abstract : Introduction . Diaper dermatitis (DD) is a common inflammatory disorder among children and infants. The objective of the present randomized and double-blind trial was to compare the therapeutic efficacies of Aloe vera cream and Calendula officinalis ointment on the frequency and severity of DD in children. Methods . Sixty-six infants with DD (aged < 3 years) were randomized to receive either Aloe cream (n = 32 ) or Calendula ointment (n = 34 ). Infants were treated with these drugs 3 times a day for 10 days. The severity of dermatitis was graded at baseline as well as at the end of trial using a 5-point scale. The adverse effects of study medications were assessed during the trial. Results . Although improvement in the severity of DD was observed in both treatment groups (P < 0.001 ), patients receiving Calendula ointment had significantly fewer rash sites compared to Aloe group (P = 0.001 ). No adverse effect was reported from either of the medications. Discussion . The evidence from this study suggests that topical Aloe and in particular Calendula could serve as safe and effective treatment for the treatment of diaper dermatitis in infants.